2020
DOI: 10.1155/2020/3580719
|View full text |Cite
|
Sign up to set email alerts
|

NFE2L2 Is a Potential Prognostic Biomarker and Is Correlated with Immune Infiltration in Brain Lower Grade Glioma: A Pan-Cancer Analysis

Abstract: Nuclear factor, erythroid 2 like 2 (NFE2L2, NRF2) is a transcription factor that regulates various antioxidant enzymes. It plays a vital physiological role in regulating oxidative stress and inflammatory response. However, the roles of NFE2L2 in human cancers are still unclear. Our study is aimed at analyzing the prognostic value of NFE2L2 in pan-cancer and at revealing the relationship between NFE2L2 expression and tumor immunity. The present study revealed that NFE2L2 was abnormally expressed and significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
71
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 62 publications
1
71
1
Order By: Relevance
“…Pan-cancer analysis could reveal the similarities and differences between different cancers and provide deep insights for the design of cancer prevention and personalized treatment strategies. A growing number of recent studies focused on genome-wide pan-cancer analysis to reveal gene mutations, RNA changes, and cancer-driving genes related to the initiation and development of cancer, which are of great significance for the early diagnosis of cancer and the identification of sensitive biomarkers [ 23 , 24 ]. The present study first comprehensively examined the expression of HSF1 in a pan-cancer dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Pan-cancer analysis could reveal the similarities and differences between different cancers and provide deep insights for the design of cancer prevention and personalized treatment strategies. A growing number of recent studies focused on genome-wide pan-cancer analysis to reveal gene mutations, RNA changes, and cancer-driving genes related to the initiation and development of cancer, which are of great significance for the early diagnosis of cancer and the identification of sensitive biomarkers [ 23 , 24 ]. The present study first comprehensively examined the expression of HSF1 in a pan-cancer dataset.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the overexpression of DNAJB6 leads to radiosensitization of glioblastoma cells 28 . Among the other eight risk‐associated genes, NFE2L2, also known as Nrf2, mediated oxidative stress and inflammatory response 29,30 . Activation of Nrf2‐Keap1 signalling up‐regulates system Xc‐, which is critical for glutathione peroxidase 4 (GPX4).…”
Section: Discussionmentioning
confidence: 99%
“…28 Among the other eight risk-associated genes, NFE2L2, also known as Nrf2, mediated oxidative stress and inflammatory response. 29,30 Activation of Nrf2-Keap1 E-F) KEGG pathway analysis based on DEGs in TCGA and CGGA signalling up-regulates system Xc-, which is critical for glutathione peroxidase 4 (GPX4). GPX4 negatively regulates ferroptosis by limiting ROS production and reducing iron intake.…”
Section: Discussionmentioning
confidence: 99%
“…Pan-cancer analysis focused on whole genome can reveal genes that are associated with the occurrence and development of cancer, providing insights into cancer diagnosis, monitoring and treatment ( 28 30 ). By analyzing NOS3 mRNA levels in normal tissues from GTEx, we found that NOS3 was expressed at the highest level in the spleen and was expressed at the lowest level in the blood.…”
Section: Discussionmentioning
confidence: 99%